2010
DOI: 10.1111/j.2042-3292.2010.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Gait deficits in liver disease: Hepatic encephalopathy and hepatic myelopathy

Abstract: Summary In this issue, the unusual clinical presentation of a horse diagnosed is described with severe liver cirrhosis and hepatic encephalopathy. The horse initially presented for thoracic and pelvic limb ataxia and weakness, and signs of forebrain disease were not apparent until later in the disease process. The typical pathology of central nervous system disease associated with liver disease is related to encephalopathy and forebrain disease; however, the spinal cord is occasionally also involved. Hepatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A diagnosis of HE was made on the basis of extreme elevations in hepatobiliary enzymes in conjunction with clinical signs of weight loss, obtunded demeanour, anorexia, hypersalivation and ataxia. These nonspecific signs are frequently reported in cases of severe hepatic impairment (West ; Nout ). An objective diagnosis of HE can be established by demonstrating hyperammonaemia, elevated serum bile acids, γ‐glutamyl transferase, aspartate transaminase and sorbitol dehydrogenase enzymes (Mair ); however, other studies have concluded that hyperammonaemia is not consistently a feature of HE (McGorum et al .…”
Section: Discussionmentioning
confidence: 97%
“…A diagnosis of HE was made on the basis of extreme elevations in hepatobiliary enzymes in conjunction with clinical signs of weight loss, obtunded demeanour, anorexia, hypersalivation and ataxia. These nonspecific signs are frequently reported in cases of severe hepatic impairment (West ; Nout ). An objective diagnosis of HE can be established by demonstrating hyperammonaemia, elevated serum bile acids, γ‐glutamyl transferase, aspartate transaminase and sorbitol dehydrogenase enzymes (Mair ); however, other studies have concluded that hyperammonaemia is not consistently a feature of HE (McGorum et al .…”
Section: Discussionmentioning
confidence: 97%